RURAL QUESTIONS AND THE PEASANTRY: AN INTERVIEW WITH TEODOR SHANIN - Alves, Vicente Eudes Lemos; Lima, Débora Assumpção e (REVISTA NERA, 2018)
From October 13 to 16, 2017, the conference "New Extractivism Peasantries and Social Dynamics: Critical Perspectives and Debates" was held in Moscow, Russia. The conference, organized annually by the BRICS Initiative in Critical Agrarian Studies, brought together experts from five continents to critically discuss agrarian issues from the perspective of Agrarian Political Economy, Geography, Sociology and Agroecology. After the conference and fieldwork, we talked with Professor Teodor Shanin about his academic background, Russian agrarian thinking, challenges and possibilities to understand the present. Professor Teodor Shanin, president of the Moscow School of Social and Economic Sciences, is an esteemed sociologist whose long-standing commitment to the study of peasant societies has led to a prolific academic career and has written more than 100 publications and important books, as “Peasants and Peasant Societies” and “Late Marx and the Russian Road: Marx and the Peripheries of Capitalism”.